The COVID-19 Vaccine: Trust, doubt, and hope for a future beyond the pandemic in Germany - Fiske, Amelia; Schoenweitz, Franziska; Eichinger, Johanna; Zimmermann, Bettina; Hangel, Nora; Sierawska, Anna; Mclennan, Stuart; Buyx, Alena (PLoS ONE, 2022)
Public perceptions of COVID-19 vaccines are critical in reaching protective levels of herd immunity. Vaccine skepticism has always been relatively high in Germany, and surveys suggest that over the course of the pandemic, enthusiasm for the COVID-19 vaccine has dropped. Looking at the period just prior to the approval of the Pfizer/BioNTech and Moderna vaccines in Germany in the latter half of 2020, this paper aims to assess the reasons for and against COVID-19 vaccine uptake among residents of Germany, and to provide in-depth qualitative data to better understand and address concerns surrounding the safety and efficacy of a COVID-19 vaccine. Our findings indicate that there is widespread trust in German institutions and health experts to provide a safe vaccine for those who need it most. However, interviewees also point to the need for more information and the centrality of support from trusted medical authorities in making individual vaccination decisions. We also present the complexity of individual positions on vaccination, and suggest that vaccine hesitancy in relation to COVID-19 needs to be understood as a nuanced, and socially malleable, territory. This indicates that the goal of a vaccination campaign is not only achieving ‘herd immunity,’ but also a social endorsement of the collaborative effort that is required for a vaccine to be successful.
CRIS-Team Scopus Importer:2023-03-08